2015
DOI: 10.1111/dme.12817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obstructive sleep apnoea on diabetic retinopathy and maculopathy: a systematic review and meta‐analysis

Abstract: There is a need for large cohort studies with long-term follow-up data to examine the long-term effects of obstructive sleep apnoea and other sleep variables on advanced retinal disease in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 31 publications
0
50
0
Order By: Relevance
“…More recently, Leong et al performed a systematic review and meta-analysis of the effect of OSA on DR and maculopathy [72]. In the systematic review, they included 16 studies: one longitudinal, the rest cross-sectional, and all the studies listed above were included, except for the two which were published later [68,70].…”
Section: Diabetic Retinopathy (Dr)mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Leong et al performed a systematic review and meta-analysis of the effect of OSA on DR and maculopathy [72]. In the systematic review, they included 16 studies: one longitudinal, the rest cross-sectional, and all the studies listed above were included, except for the two which were published later [68,70].…”
Section: Diabetic Retinopathy (Dr)mentioning
confidence: 99%
“…In a review article from 2005, Sinclair and colleagues commented that to control DR, prompt detection was necessary, along with the management of "common systemic comorbid conditions such as hypertension, hyperlipidemia, anemia, obstructive sleep apnea, and smoking--all of which tend to accelerate its course and increase its severity" [73]. In their recent systematic review and metaanalysis, Leong et al also concluded that the effect of CPAP on DR and diabetic macular oedema needed assessment through randomised controlled trials [72].…”
Section: Cpap and Diabetic Retinopathymentioning
confidence: 99%
“…There has been increasing evidence on the relationship between OSA and increased risk or severity of DR [7,8]. Longitudinal data have also shown that OSA is a risk factor for DR progression and that treatment with continuous positive airway pressure reduced this risk [6].…”
Section: Discussionmentioning
confidence: 99%
“…To this end, sleep and sleep disturbances such as obstructive sleep apnea (OSA) have recently surfaced as a potential modifiable risk factor for DR. While OSA has been relatively more established as a risk factor for DR [6][7][8], evidence on associations between sleep duration and DR have been lacking and inconsistent [9][10][11][12]. Furthermore, these four studies were based on self-reported sleep duration that is subject to recall bias.…”
mentioning
confidence: 99%
“…27 Patients with mild reduction in arterial hemoglobin saturation due to sleep apnoea have more severe retinopathy than those whose airways do no obstruct at night. Positive pressure ventilation in such patients also reduces the rate of progression of DR. [28][29][30][31][32] Does illuminating the retina reduce the risk of progression of retinopathy?…”
Section: Evidence That Oxygen Supplementation Improves Visual Functiomentioning
confidence: 99%